(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Diabetes mellitus (DM), particularly Type 2 DM is now recognized as a major chronic public health problem throughout the world. Different anti-diabetic agents, oral or injectable are used to regulate patients’ glycemic status as monotherapy or in combination. Objectives: To observe the prescribingpattern ofanti-diabetic agents and to collect demographic and disease details of type 2 DM patients. Materials and Methods: This descriptive cross-sectional study was conducted from January to August 2017 in the outpatient department of Border Guard Hospital, Pilkhana; a tertiary level hospital in Dhaka. The study enrolled 172 type 2 diabetic patients purposively on specified criteria. Demographic data,drug prescribing pattern, disease pattern were collected by an interview and from patients’ prescriptions. Results: Among 172 respondents,70 (40.70%) were male and 102 (59.30%) were female. The mean age of patients was 54.21±10.09 years. Eighty seven (50.58%) patients were either overweight or obese. Eighty two (47.67%) patients had family history of DM. Majority of patients (84.89%) had duration of diabetes >5 years and 84 (48.84%) patients had co-morbidities. Majority of the patients 135(78.49%) were prescribed oral drugs either alone or in combination. Among them 83 (63.48%) patients were prescribed oral monotherapy and 52(38.52%) patients were prescribed oral combination therapy. Metformin was the most prescribed oral anti-diabetic drug as monothearpy (71.08%). Among combined anti-diabetic drugsbased on class, metformin+Dipeptidyl peptidase 4 inhibitors(DPP4i) (36.11%), combination was the most commonly prescribed combination. The findings can lead to select the formulation and combination of anti-diabetic drugs in this part of the world for developing & marketing a new anti-diabetic drug. Conclusion: Metformin was the most commonly prescribed drug both as monotherapy as well as combination therapy and monotherapy was predominant over combination therapy. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 139-143